Emotional Intelligence of Malaysian University Students Using Non-Parametric Approach - Siti Noor Asyikin, Mohd Razali (Institute of Engineering Mathematics, Universiti Malaysia Perlis, 2018)
Link to publisher's homepage at http://amci.unimap.edu.my